FRI0122 Eular 2015 Recommendations for Cardiovascular Risk Could Radically Change Patients Care in Chronic Inflammatory Rheumatisms. (15th July 2016) - Daien, C.; Tubery, A.; Du Cailar, G.; Mura, T.; Picot, M.C.; Bourret, R.; Roubille, F.; Bousquet, J.; Morel, J.; Fesler, P.; Combe, B.
Abstract : Background: Patients with chronic inflammatory rheumatic disease have a greater risk of cardiovascular (CV) diseases. European recommendations of cardiology propose to classify patients with asymptomatic atheromatous plaques as high CV risk patients. New EULAR recommendations about CV risk management propose the use of supra-aortic vessel ultrasound for atheromatous plaques detection and total CV risk estimation. Moreover, EULAR-2015 recommendations suggest multiplying by a 1.5 factor the global CV risk for all patients with Rheumatoid Arthritis (RA) unlike 2010 recommendations. Objectives: The objective of our study was to evaluate the impact of these new recommendations on CV management, especially on indication of statin use, in patients with RA in daily practice, in comparison to EULAR-2010 recommendations. Methods: Total CV risk estimation included physical examination, glucidic and lipidic blood tests, supra-aortic and abdominal vessels ultrasound, echocardiography and global risk SCORE calculation. Heart-SCORE was multiplied according to EULAR-2010 (mSCORE2010) or EULAR-2015 (mSCORE2015) recommendations. For EULAR-2015 recommendations, patients with ultrasound carotid plaques were classified at high CV risk. LDL targets and immediate need of statin use were defined according to European cardiology recommendations with need of statin when LDL >0.7 g/L for patients at very high CV risk and >1 g/L for those at high risk. In moderate and low risk patients, statins are not immediately recommended. Results: 157 RA patients underwent the screening with a mean disease duration of 13 (6–19) ± 9 years and mean age of 61 ± 11 years. 56/76 (73.7%) of patients classified as moderate risk with Heart-SCORE and 3/12 (25%) of patients with low risk had asymptomatic carotid plaques. Application of the EULAR 2010 recommendations should lead to immediate statin prescription in 42 patients (28%) whereas applications of the EULAR 2015 recommendations should lead to statin prescription in 92 (61%) patients. Conclusions: In our experience, the use of carotid ultrasound to estimate total CV risk and thus to define LDL targets led to prescribe statins in 61% of patients with RA. Disclosure of Interest: None declared